Case report: incessant ventricular fibrillation in a conscious left ventricular assist device patient. Issue 9 (7th September 2021) - Jakstaite, Aiste Monika; Luedike, Peter; Wakili, Reza; Kochhäuser, Simon; Ruhparwar, Arjang; Rassaf, Tienush; Papathanasiou, Maria
Abstract: Background : Ventricular arrhythmia in left ventricular assist device (LVAD) recipients represents a challenging clinical scenario and the optimal treatment strategy in this unique patient population still needs to be defined. Case summary : We report on a 61-year-old LVAD patient with incessant ventricular fibrillation (VF) despite multiple unsuccessful attempts to restore normal rhythm with external defibrillation and antiarrhythmic medication. He remained initially stable as an outpatient and subsequently developed secondary organ failure. Discussion : This case demonstrates that under LVAD support long-term haemodynamic stability is possible even in case of VF, a situation that resembles Fontan circulation. However, ventricular arrhythmias are associated with a high risk of secondary organ damage due to right heart failure if left untreated. In case of refractory ventricular tachycardia or electrical storm listing for heart transplantation with high priority status should be pursued when possible. Alternatively, catheter ablation may be considered in selected cases and be performed in experienced centres in close collaboration with all involved specialists.